Stability Analysis Of Anti-islanding Protection Based On Positive Feedback Technique - Battistel , Andrei Giordano Holanda; Jaskulski , Igor Weide; Pinheiro, Humberto (Eletrônica de Potência, 2011)
This paper develops a stability analysis of a local Islanding Detection Algorithm (IDA) based on positive feedback technique that has no Non Detection Zone (NDZ). A complete dynamic model for the system is derived and the stability analysis with Nyquist stability criterion is carried out. It is demonstrated that the parameters of the IDA can be easily tuned at the key operating conditions to guarantee the under or over voltage relay tripping whenever islanding occurs. Finally, experimental results are presented to support the theoretical analysis developed.